The going to bed book - Boynton, Sandra (New York : Little Simon, 2004)
An assortment of animals on a boat take a bath, put on their pajamas, brush their teeth, and exercise before going to bed.
Cover title.
On board pages.
Keywords: Children -- Sleep -- Juvenile fiction; Night -- Juvenile fiction; Sleep -- Juvenile fiction; Bedtime -- Juvenile fiction; Animals -- Juvenile fiction; Stories in rhyme -- Juvenile fiction; Board books -- Juvenile fiction